Better than the movies ebook - Painter, Lynn (Better Than the Movies, 2021)
A USA TODAY and New York Times bestseller Perfect for fans of Kasie West and Jenn Bennett, this "sweet and funny" (Kerry Winfrey, author of Waiting for Tom Hanks ) teen rom-com follows a hopelessly romantic teen girl and her cute yet obnoxious neighbor as they scheme to get her noticed by her untouchable crush. Perpetual daydreamer Liz Buxbaum gave her heart to Michael a long time ago. But her cool, aloof forever crush never really saw her before he moved away. Now that he's back in town, Liz will do whatever it takes to get on his radar—and maybe snag him as a prom date—even befriend Wes Bennet. The annoyingly attractive next-door neighbor might seem like a prime candidate for romantic comedy fantasies, but Wes has only been a pain in Liz's butt since they were kids. Pranks involving frogs and decapitated lawn gnomes do not a potential boyfriend make. Yet, somehow, Wes and Michael are hitting it off, which means Wes is Liz's in. But as Liz and Wes scheme to get Liz noticed by Michael so she can have her magical prom moment, she's shocked to discover that she likes being around Wes. And as they continue to grow closer, she must reexamine everything she thought she knew about love—and rethink her own ideas of what Happily Ever After should look like.